2019
DOI: 10.1021/acsomega.9b02819
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Effects on Pigment Coatings: Pigment Red 179 as a Case Study

Abstract: Here, we have studied, with a combined experimental and computational approach, the effect of the crystal environment and aggregation on the electronic properties of Pigment Red 179, which affect both its color and optical energy gap. Spectra acquired in the near-infrared and visible range of energies suggest that this molecule is indeed a “cool” dye, which can be employed as a red pigment that provides effective color coverage to different substrates without contributing to their heating during light irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 51 publications
(82 reference statements)
1
23
0
Order By: Relevance
“…Thus, the ordered molecular arrangement with strong aromatic cycle stacking in the single crystals leads to NIR absorption (Figure ). It has been recently shown that the increasing concentration of PDI dye in a polymer matrix leads to strong intermolecular aromatic stacking that strongly influences on the absorption . In contrast, solid state fluorescence studies showed clear red fluorescence for PDI‐80, PDI‐120 and PDI‐130, however, fluorescence has been completely quenched for PDI‐180 and PDI‐250 (Figure ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, the ordered molecular arrangement with strong aromatic cycle stacking in the single crystals leads to NIR absorption (Figure ). It has been recently shown that the increasing concentration of PDI dye in a polymer matrix leads to strong intermolecular aromatic stacking that strongly influences on the absorption . In contrast, solid state fluorescence studies showed clear red fluorescence for PDI‐80, PDI‐120 and PDI‐130, however, fluorescence has been completely quenched for PDI‐180 and PDI‐250 (Figure ).…”
Section: Resultsmentioning
confidence: 96%
“…It has been recently shown that the increasing concentration of PDI dye in a polymer matrix leads to strong intermolecular aromatic stacking that strongly influences on the absorption. [47] In contrast, solid state fluorescence studies showed clear red fluorescence for PDI-80, PDI-120 and PDI-130, however, fluorescence has been completely quenched for PDI-180 and PDI-250 ( Figure 3). The digital images also showed strong quenching of fluorescence for PDI-180 and PDI-250 whereas PDI-80, PDI-120 and PDI-130 showed red fluorescence (Figure 4).…”
Section: Introductionmentioning
confidence: 91%
“…The model expected to reproduce the absorption behavior in an aggregate phase, referred to as crystal‐embedded and described in the computational details in the crystal embedded calculation section, yields instead a less structured spectrum, with significant absorption in the 300–700 nm range of wavelengths, thus spanning a large portion of the visible range (as expected from a black material). The nature of the first excitation (I* in Figure 1) is also different, with a more pronounced intermolecular charge‐transfer character, a behavior found also in the TD‐DFT study of so‐called Paliogen Red molecule (or Pigment Red 179) [ 39 ] when simulated embedded into a crystal. The D CT [ 45 ] quantum descriptor for charge transfer suggests an hole‐electron distance of ≈3.15 Å, to be compared with an intermolecular distance between P‐black molecules in the crystal of ≈3.4 Å.…”
Section: Figurementioning
confidence: 87%
“…The molecular structure of P-black molecules was relaxed in the ground electronic state (GS) using the Gaussian 16 package, [48] adopting the B3LYP exchange and correlation functional [49,50] in conjunction with 6-31+G(d,p) basis set and Grimme's D3-BJ dispersion correction: [51] this level of theory proved to be suitable in a previous investigation on a similar system (dye Paliogen Red). [39] All relaxed structures are potential energy minima, as all normal modes have a positive frequency. Calculations of electronic excited states were performed with the timedependent density functional theory (TDDFT) approach using the rangeseparated exchange and correlation functional CAM-B3LYP, [52] to better describe charge-transfer transitions and the spectral shape.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation